Emotion Recognition Recent Advances, New Perspectives and Applications - Abed Hosseini, Seyyed (IntechOpen, 2023)
Emotion is a complex phenomenon that varies from person to person. Different emotional states of a person can be inferred through external and internal reactions that change in different situations. Emotion recognition has become a research milestone in cognitive science, neuroscience, computer science, psychology, artificial intelligence, and other areas. Emotion recognition research uses non-physiological signals such as facial expression, speech, and body movement, as well as physiological signals and images such as electrical skin resistance (GSR), heart rate (HR), electrocardiogram (ECG), functional magnetic resonance imaging (fMRI), electroencephalogram (EEG) and magnetoencephalogram (MEG). This book provides a comprehensive overview of the different techniques used in emotion recognition and discusses recent developments, perspectives, and applications in the field.